2007
DOI: 10.1038/nmeth1017
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution three-dimensional imaging of large specimens with light sheet–based microscopy

Abstract: We report that single (or selective) plane illumination microscopy (SPIM), combined with a new deconvolution algorithm, provides a three-dimensional spatial resolution exceeding that of confocal fluorescence microscopy in large samples. We demonstrate this by imaging large living multicellular specimens obtained in a three-dimensional cell culture. The ability to rapidly image large samples at high resolution with minimal photodamage provides new opportunities especially for the study of subcellular processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
220
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(223 citation statements)
references
References 12 publications
1
220
0
2
Order By: Relevance
“…It has been shown that performing multi-view reconstructions with SPIM data can yield improved imaging in many situations [21][22][23]. However, for the system in this study this technique is not useful because the organ of interest is a small bundle of cells in a concavity on a much larger organism, and the range of angles from which useful views can be obtained is quite limited.…”
Section: Sample Rotation Optimizes Imaging Accessmentioning
confidence: 99%
“…It has been shown that performing multi-view reconstructions with SPIM data can yield improved imaging in many situations [21][22][23]. However, for the system in this study this technique is not useful because the organ of interest is a small bundle of cells in a concavity on a much larger organism, and the range of angles from which useful views can be obtained is quite limited.…”
Section: Sample Rotation Optimizes Imaging Accessmentioning
confidence: 99%
“…In contrast, csiLSFM applies an obvious but stable method to create the interference pattern reaching the finest limit. Additionally, csiLSFM is capable of rotating the specimen and implementing multiple-views imaging to improve the axial resolution (41,42). Lower wavelengths can be used that work well with smaller molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Dans une MFL, le système de détection consiste en un microscope à épifluorescence classique : un objectif, un fil- exemples [24,25]). De plus, l'excellent rapport signal/bruit de la MFL permet l'utilisation simultanée de techniques de traitement d'images, comme la déconvolution, et la fusion des différentes vues [26]. Ces techniques de reconstruction 3D ont été utilisées avec succès sur des embryons de medaka [20], des embryons de poisson zèbre ( Figure 4B), des follicules ( Figure 4A et Vidéo 1 1 ) et des embryons de drosophile [19,24,25], des drosophiles adultes ( Figure 4D et Vidéo 2 1 ) et de cellules épithéliales sous forme de kystes ou de sphéroïdes [27].…”
Section: Une Approche Différente : La Microscopie De Fluorescence à Funclassified
“…En raison du flux de photons atteignant le détecteur, la MFL permet une acquisition avec un très bon rapport signal/bruit (de l'ordre de 1 000:1 en mode rapide), bien plus élevé que pour les microscopes confocaux ou biphotoniques. Un des autres avantages de la MFL est l'imagerie à grande gamme dynamique qui permet d'effectuer de la déconvolution pour accroître la résolution spatiale [26] et de quantifier de manière très précise la distribution de la fluorescence d'une protéine marquée. Par exemple, dans les expériences sur les embryons de poisson zèbre, les variations de l'intensité des noyaux cellulaires, dont l'ADN était marqué, ont permis de déterminer le niveau de compaction de l'ADN sans aucune sonde fluorescente supplémentaire [18] (Figure 4C).…”
Section: Signal Et Acquisitionunclassified